Public policy implications of entrepreneurship research - Aguinis, Herman; Jensen, Søren H.; Kraus, Sascha; Poček, Jasna; Pinelli, Michele (International Small Business Journal: Researching Entrepreneurship, 2025)
After examining 4247 articles in 10 journals between 2010 and 2020, we found only 11.7% (n = 497) included explicit policy recommendations, and just 1.4% (n = 60) had explicit policy implications subsections. We analysed these 60 articles using behaviourally anchored rating scales (BARS) to assess four key aspects of the policy implications for quality and practicality. Policy implications were generally based on methodologically transparent research, but often lacked rigour in detailing policy and regulatory requirements, and typically demanded significant resources for implementation. Our results contribute to theory by improving our understanding of the why, when and how of policy implications of entrepreneurship research. Also, our BARS framework allows for a differentiation between quality and practical applicability, thereby reframing assumptions by showing that impactful policy implications require both methodological quality and implementation feasibility. Overall, the research–policy gap in entrepreneurship results not merely from disengagement but also research–policy misalignment in content and form.
Keywords: entrepreneurship; policy implications; public policy; research impact